1999
DOI: 10.1007/bf03012976
|View full text |Cite
|
Sign up to set email alerts
|

Second stage pushing correlates with headache after unintentional dural puncture in parturients

Abstract: Purpose: To determine the association between bearing down, postdural puncture headache (PDPH) and epidural blood patch (EBP) following single 17 gauge unintentional dural puncture (UDP) in parturients. Methods: The charts of 60 parturients identified with UDP in our institutional database during epidural placement were independently reviewed. Patients were divided into categories based on the anesthetic record: well-documented single punctures; well-documented multiple punctures; catheter-related puncture; un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(22 citation statements)
references
References 15 publications
0
18
0
4
Order By: Relevance
“…Compared with spontaneous vaginal delivery, previous studies have observed reduced PDPH and EBP rates with either instrumental vaginal 20 or caesarean delivery; 21 bearing-down during the active part of the second stage of labour is generally accepted as the reason. Ravindran et al, 22 however, observed no association between bearing-down and PDPH or EBP rates, and current practice does not preclude bearing-down nor does it advise instrumental delivery to minimise headache rates.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with spontaneous vaginal delivery, previous studies have observed reduced PDPH and EBP rates with either instrumental vaginal 20 or caesarean delivery; 21 bearing-down during the active part of the second stage of labour is generally accepted as the reason. Ravindran et al, 22 however, observed no association between bearing-down and PDPH or EBP rates, and current practice does not preclude bearing-down nor does it advise instrumental delivery to minimise headache rates.…”
Section: Discussionmentioning
confidence: 94%
“…Respondents infrequently altered management of the second stage of delivery. Older reports examining the efficacy of this practice involved low numbers and reported conflicting results [28,29]. Abdominal binder use has been reported as low in all surveys, as no study has demonstrated its efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…[50][51][52][53] The increased incidence of post-dural puncture headache in parturients may be attributed to numerous factors including peripartum dehydration, which could reduce the production of CSF, postpartum diuresis, abrupt release of intra-abdominal pressure and venacaval compression at delivery, which reduces epidural venous pressures. Maternal bearing-down efforts that could increase CSF leakage through the dural hole could also be a factor, as well as early ambulation, anxiety about delivery and hormonally-induced ligamentous changes.…”
Section: Discussionmentioning
confidence: 99%